Financial Performance of Hospital during Pandemic Covid 19 - Farid Fauzan Mahubessy; Ede Surya Darmawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Corona virus is known to have originated from the Wuhan city China, starting December 2019 years. Data from March 30, 2020, more than 170 countries reported a number of positive cases of Covid-19 as many as 720,117, including Indonesia. The hospital experienced a decrease in revenue but the hospital still guaranteed patient recovery in accordance with hospital service standards. This will affect the financial strategy that can be used in dealing with the pandemic by analyzing financial performance through SWOT analysis in hospitals with profitability ratios (Strength, Weakness, Opportunity, and Threat). We include research for the 2020 period, types of national and international articles published in the field of public and hospital health connected to the COVID-19 pandemic relating to infirmary financial strategies with a SWOT analysis. Conducted a search, using a multi-method strategy between January 2020 and December 2020. In carrying out the search, if any, complete download references, quotes and abstracts to Vancouver, the database reference program, for further evaluation. Systems thinking for decision making, several hospital strategies are needed to survive this pandemic, namely a change in leadership style in terms of financial management by not only focusing on COVID-19 but essential services for other diseases can be improved with rapid and comprehensive preparation and response using an integrated health system understanding in every hospital stakeholder.